The Influence of Servant Leadership Behavior to Corporate Culture Based on the OCAI Model - Zhihua Deng, Jing Lv, Xiaohong Xiao (Design Engineering, 2020)
Related studies have shown that servant leadership behavior has fine promoting effects to employees’ behavior. However, its mechanism and effect on the organizational culture are not very clear. Based on the literature research of this field, this study established a theoretical model in which servant leadership impact on organizational culture. The authors take 421 effective samples in Chinese situation as the research object and use statistical analysis software like SPSS and SEM, and take empirical methods such as the descriptive statistical analysis, correlation analysis and hypothesis testing. Data analysis indicates that the servant leadership behavior possess significantly positive influence to corporate culture that is to say marketable culture, clan culture and adhocracy culture, and possess significantly negative effect to hierarchical culture. The result has positive significance to contingency application of leadership behavior and the construction of corporate culture.